2012
DOI: 10.1021/es204272v
|View full text |Cite
|
Sign up to set email alerts
|

Organophosphorus Flame Retardants and Plasticizers in Airborne Particles over the Northern Pacific and Indian Ocean toward the Polar Regions: Evidence for Global Occurrence

Abstract: Organophosphorus compounds (OPs) being applied as flame retardants and plasticizers were investigated in airborne particles over the Pacific, Indian, Arctic, and Southern Ocean. Samples taken during two polar expeditions in 2010/11, one from East Asia to the high Arctic (CHINARE 4) and another from East Asia toward the Indian Ocean to the Antarctic (CHINARE 27), were analyzed for three halogenated OPs (tris(2-chloroethyl) phosphate (TCEP), tris(2-chloroisopropyl) phosphate (TCPP) and tris(1,3-dichloro-2-isopro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

28
177
9
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 254 publications
(217 citation statements)
references
References 38 publications
28
177
9
3
Order By: Relevance
“…As a result, they are now widely present in various environmental matrices worldwide, including water (Wang et al, 2011;Rodil et al, 2005;Marklund et al, 2005), soil Mihajlovic et al, 2011), air (Moller et al, 2011;Moller et al, 2012), sediment (Cristale and Lacorte, 2013) and biota (Kim et al, 2011). Moreover, OPEs have already been detected in human milk (Sundkvist et al, 2010) and their metabolites were also found in human urine (van den Eede et al, 2013;Reemtsma et al, 2011;Schindler et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…As a result, they are now widely present in various environmental matrices worldwide, including water (Wang et al, 2011;Rodil et al, 2005;Marklund et al, 2005), soil Mihajlovic et al, 2011), air (Moller et al, 2011;Moller et al, 2012), sediment (Cristale and Lacorte, 2013) and biota (Kim et al, 2011). Moreover, OPEs have already been detected in human milk (Sundkvist et al, 2010) and their metabolites were also found in human urine (van den Eede et al, 2013;Reemtsma et al, 2011;Schindler et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Lysine, cadaverine, acridine orange (AO), cucurbit [7]uril (CB7), lysine decarboxylase (LDC, from Bacterium cadaveris), 2,4,6-trinitrebenzenesulfonic acid (TNBS), and 1,7-diaminoheptane (DAH) were purchased from Sigma-Aldrich (St. Louis MO, USA). Guanosine 5 0 -diphosphate, 3 0 -diphosphate (ppGpp) was obtained from Trilink BioTechnologies (San Diego, CA).…”
Section: Chemicals and Materialsmentioning
confidence: 99%
“…In this paper, inhibitory effect of twelve OPEs with aromatic, alkyl or chlorinated alkyl substituents on the activity of lysine decarboxylase (LDC) was assessed quantitatively with an economic and label-free fluorescence sensor and cell assay. The sensor comprises a macrocyclic host (cucurbit [7]uril) and a fluorescent dye (acridine orange) reporter. The twelve OPEs were found to vary in their capacity to inhibit LDC activity.…”
mentioning
confidence: 99%
“…As a result, OPEs are now widely present in indoor and outdoor environments, such as in surface water (Wang et al, 2011;Bacaloni et al, 2008), ground water (Regnery et al, 2011), and wastewater (Rodil et al, 2005;Marklund et al, 2005), as well as in airborne particles (Möller et al, 2011(Möller et al, , 2012, indoor dust (Marklund et al, 2003;Van den Eede et al, 2012;Yang et al, 2014) and soils (Fries and Mihajlovic, 2011). Moreover, OPEs in the environment can enter the bodies of animals and humans via skin (Möller et al, 2012), the respiratory system, and diet. Currently, OPEs have already been detected in marine and fresh water biota (Sundkvist et al, 2010;Kim et al, 2011), human milk (Sundkvist et al, 2010), and human plasma (Shah et al, 2006), and their metabolites were also found in human urine (Reemtsma et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…The main toxic effects included eye and skin irritation, carcinogenicity, dermatitis, and neurotoxicity (Möller et al, 2012;Van den Eede et al, 2012). For example, tricresyl phosphate (TCrP) shows delayed neurotoxicity (Craig and Barth, 1999), and chlorinated OPEs are considered to be potentially carcinogenic (Ni et al, 2007).…”
Section: Introductionmentioning
confidence: 99%